2014
DOI: 10.1007/s00018-014-1744-7
|View full text |Cite
|
Sign up to set email alerts
|

Generation of CRISPR/Cas9-mediated gene-targeted pigs via somatic cell nuclear transfer

Abstract: The domestic pig has been widely used as an important large animal model. Precise and efficient genetic modification in pig provides a great promise in biomedical research. Recently, clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated (Cas) system has been successfully used to produce many gene-targeted animals. However, these animals have been generated by co-injection of Cas9 mRNA and single-guide RNA (sgRNA) into one-cell stage embryos, which mostly resulted in mosaicism of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
173
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(181 citation statements)
references
References 25 publications
5
173
0
Order By: Relevance
“…Despite the demonstration that CRSPR/Cas9 works in livestock cells, recovery of CRISPR mutant cell clones was much lower than that with TALENs, suggesting that CRISPR/Cas9 system needs further optimization to achieve targeting efficiencies comparable to TALENs. Follow-up studies have demonstrated that CRISPR/Cas9 genomeedited cells can support development to term when used as nuclear donor in SCNT in pigs [244][245][246] and goats [247].…”
Section: Application Designer Nucleasesmentioning
confidence: 99%
“…Despite the demonstration that CRSPR/Cas9 works in livestock cells, recovery of CRISPR mutant cell clones was much lower than that with TALENs, suggesting that CRISPR/Cas9 system needs further optimization to achieve targeting efficiencies comparable to TALENs. Follow-up studies have demonstrated that CRISPR/Cas9 genomeedited cells can support development to term when used as nuclear donor in SCNT in pigs [244][245][246] and goats [247].…”
Section: Application Designer Nucleasesmentioning
confidence: 99%
“…One-step generation of mutants, which means that biallelic targeting with efficiency close to 100 % is achieved, has been published in pigs, for example, for the von Willebrand Factor gene [67] using zygote injections of sgRNAs and Cas9. CRISPR/Cas9 targeting in cell lines followed by SCNT can also reduce the need for breeding as it has been exemplified by generation of PARK2 -/-PINK1 -/-double mutant for modeling Parkinson"s disease [68]. Multiple knock-in strategies have also been developed in the pig, one interesting example of which is Oct4-tdTomato pig transgenic reporter line produced using SCNT, where expression of tdTomato was present in pluripotent cells of the embryos [69].…”
Section: Crispr/cas9 In Animal Modelsmentioning
confidence: 98%
“…In addition, they demonstrated that blastocyst complementation is reproducible in pigs by using somatic cell nuclear transfer (cloning) technology [51]. New emerging genome-modifying technology, e.g., TALENs or the CRISPR/Cas9 system, has made the construction of organ-deficient pigs simpler and more convenient [52][53][54]. although several options have been proposed to resolve such a concern [56].…”
Section: Blastocyst Complementationmentioning
confidence: 99%